Extreme Environmental Events c - Meyers, Robert A.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Extreme Environmental Events is an authoritative single source for understanding and applying the basic tenets of complexity and systems theory, as well as the tools and measures for analyzing complex systems, to the prediction, monitoring, and evaluation of major natural phenomena affecting life on earth. These phenomena are often highly destructive, and include earthquakes, tsunamis, volcanoes, climate change,, and weather. Early warning, damage, and the immediate response of human populations to these phenomena are also covered from the point of view of complexity and nonlinear systems. In 61 authoritative, state-of-the art articles, world experts in each field apply such tools and concepts as fractals, cellular automata, solitons game theory, network theory, and statistical physics to an understanding of these complex geophysical phenomena.
Complexity in Earthquakes, Tsunamis, and Volcanoes, and Forecast -- Complexity in Human Reaction to Extreme Events -- Climate Modeling, Global Warming and Weather Prediction.
Keywords: Environmental sciences; Mathematical geography; Physical geography; Climatic changes; Environment; Geophysics/Geodesy.; Geophysics and Environmental Physics; Environmental Monitoring/Analysis.; Climate Change; Computer Applications in Earth Sciences